IMMUNOSTIMULATING PROPERTIES OF NATURAL CHEMICAL COMPOUNDS CONTAINED IN BARBERRY FRUITS (Scientific journal of the Fergana State University, 2023)
This article is about the chemical composition of the fruit of the plant Berberis oblonga Schneid , found in the foothills, hills and gardens of the Republic of Uzbekistan, and on this basis to obtain a new medicinal biologically active supplement. First, the fruit was extracted at low temperature with a solution of water-ethanol (70-30) using a vacuum extractor type TN-300. The fact that the medicinal plant is rich in biologically active substances is especially important because it retains a lot of bioflavonoids and organogenic elements. It has immunostimulatory properties because it stores vitamins, micro-and macro-biogenic elements necessary for the human immune system. Due to the fact that the plant contains substances such as vitamin C, which have antioxidant activity, it is possible to obtain natural healing food supplements that have a high antioxidant effect.